PENGARUH KECERDASAN EMOSIONAL PEMIMPIN TERHADAP KINERJA TIM SISTEM INFORMASI - Indah Lestari; Apprilia Faradita (Pojok Publisher, 2025)
This study investigates the vital role of a leader's emotional intelligence (EI) in driving the performance of information systems (IS) teams working under high pressure. Given the intensity of today's IS team work environment, this study addresses the need to understand the non-technical factors that contribute to success. Through a systematic literature review method encompassing empirical research spanning the period from 2010 to 2024, strong evidence was found to support the primary hypothesis. A thematic analysis of the existing literature identified that the three pillars of leader EI—self-awareness for managing personal stress, empathy for understanding team members' emotional states, and relationship management for navigating conflict and motivating—were strong predictors of team performance. Furthermore, the study revealed that these positive influences were largely mediated by the creation of psychological safety. A psychologically safe environment enables open communication, encourages healthy risk-taking, and accelerates the cycle of learning from failure, all of which are crucial in IS projects. These findings provide practical implications for organizations to prioritize EI development in leadership training programs and make it a critical criterion in the selection of IS project managers, in order to build resilient, innovative, and high-performing teams.